Structure-insensitive switchable terahertz broadband metamaterial absorbers. (28th May 2019) - Qi, Limei; Liu, Chang; Zhang, Xia; Sun, Dandan; Shah, Syed Mohsin Ali
Abstract: A nearly structural-insensitive switchable broadband terahertz metamaterial absorber is proposed, which consists of several gold rods and a vanadium dioxide (VO2 ) ground plane separated by a dielectric spacer. By controlling the temperature of VO2, state of the absorber can be switched from "on" to "off" in the frequency range of 1.116–1.564 THz. The physical mechanism of the absorber is given based on the wave-interference theory and field distributions. Interestingly, the proposed absorber shows a similar performance for random arrangements of a given number of rods on the top layer, which could greatly reduce the requirement of fabrication accuracy.